Implications Of Surah Al-Hujurat Verse 13 In Realizing Harmonization Of A Multicultural Society - Kasmiati; Arbi (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2024)
This study explores the implications of Surah Al-Hujurat Ayat 13 in promoting social harmony within Indonesia’s multicultural society, aligning with the nation’s foundational values in Pancasila. Using a qualitative approach and literature review method, the research highlights two key internalization strategies: 1) strengthening the role of families in providing Islamic education, and 2) incorporating multicultural education into formal schooling. The values found in Surah Al-Hujurat Ayat 13 reflect Pancasila’s principles, especially the second (Just and Civilized Humanity), third (Unity of Indonesia), and fifth (Social Justice for All). This alignment underscores the relevance of Islamic teachings in fostering social cohesion, emphasizing the role of both family and formal education in building harmony.